A Low‐Cost and Scalable Carbon Coated SiO‐Based Anode Material for Lithium‐Ion Batteries. Issue 3 (25th January 2021) - Huang, Zhihao; Dang, Guoju; Jiang, Wenping; Sun, Yuanyu; Yu, Meng; Zhang, Quansheng; Xie, Jingying
Abstract: Silicon monoxide (SiO) is considered as one of the most promising alternative anode materials thanks to its high theoretical capacity, satisfying operating voltage and low cost. However, huge volume change, poor electrical conductivity, and poor cycle performance of SiO dramatically hindered its commercial application. In this work, we report an affordable and simple way for manufacturing carbon‐coated SiO−C composites with good electrochemical performance on kilogram scales. Industrial grade SiO was modified by carbon coating using cheap and environment friendly polyvinyl pyrrolidone (PVP) as carbon source. High‐resolution transmission electron microscopy (HRTEM) and Raman spectra results show that there is an amorphous carbon coating layer with a thickness of about 40 nm on the surface of SiO. The synthesized SiO−C‐650 composite shows great electrochemical performance with a high capacity of 1491 mAh.g −1 at 0.1 C rate and outstanding capacity retention of 67.2 % after 100 cycles. The material also displays an excellent performance with a capacity of 1100 mAh.g −1 at 0.5 C rate. Electrochemical impedance spectroscopy (EIS) results also prove that the carbon coating layer can effectively improve the conductivity of the composite and thus enhance the cycling stability of SiO electrode. Abstract : Cheap oxide anode material : A mechanical milling process followed by heat treatment(carbonization)is adopted to synthesize SiO−C‐650 composite, in which industrial grade polyvinyl pyrrolidone is chosen as single carbon source. As anode of Li‐ion batteries, SiO−C‐650 exhibits a stable capacity of 1491 mAh g −1 at a current density of 0.1 C, capacitance retention is 67.2 % after 100 cycles at 0.1 C. This is a feasible industrial method because it is simple and involves low‐cost materials.